Synthesis, structure and reactivity of a cyapho-cyanamide salt - Ergöçmen, D; Goicoechea, JM (Wiley, 2021)
We describe a facile synthesis of the cyapho-cyanamide salt [Na(18-crown-6)][N(CN)(CP)] from reaction of [Na(18-crown-6)][PH2] (18-crown-6=1,4,7,10,13,16-hexaoxacyclooctadecane) with dimethyl N-cyanocarbonimidate, (MeO)2C=N(CN). The reaction proceeds with elimination of two equivalents of methanol. Careful tuning of the reaction conditions allowed for the isolation and characterization of the N-cyano(carboximidate)phosphide intermediate [HP{C(OMe)N(CN)}]−. Due to the adverse effects of methanol in these reaction mixtures, a bulk scale synthesis of [Na(18-crown-6)][N(CN)(CP)] could be achieved by addition of a base (LiHMDS) to neutralize the resulting alcohol. Further reactivity studies of this anion reveal that functionalization at the phosphorus atom is viable to yield a new family of cyanide-functionalised phosphorus heterocycles.